Effects on the food-web structure and bioaccumulation patterns of organic contaminants in a climate-altered Bothnian Sea mesocosms - Berglund, Åsa M. M.; Gallampois, Christine; Ripszam, Matyas; Larsson, Henrik; Figueroa, Daniela A.; Grinienė, Evelina; Byström, Pär; Gorokhova, Elena; Haglund, Peter; Andersson, Agneta; Tysklind, Mats (Frontiers in Marine Science, 2023)
Climate change is expected to alter global temperature and precipitation patterns resulting in complex environmental impacts. The proposed higher precipitation in northern Scandinavia would increase runoff from land, hence increase the inflow of terrestrial dissolved organic matter (tDOM) in coastal regions. This could promote heterotrophic bacterial production and shift the food web structure, by favoring the microbial food web. The altered climate is also expected to affect transport and availability of organic micropollutants (MPs), with downstream effects on exposure and accumulation in biota. We performed a mesocosmsstudy to assess climate-induced changes in a Bothnian Sea food web structure as well as bioaccumulation patterns of MPs, focusing on aquatic food webs with fish as top predator.The treatments included increased temperature and tDOM alongside addition of MPs. The tDOM addition affected nutrient availability and boosted both phytoplankton and heterotrophic bacteria in our fairly shallow mesocosms. The increased tDOM further benefitted flagellates, ciliates and mesozooplankton, while the temperature increase and MP addition had minor effect on those organism groups. Temperature, on the other hand, had a negative important on fish growth and survival, wereas tDOM and MP addition only had minor impact on fish. Moreover, there were indications that bioaccumulation of MPs in fish either increased with tDOM addition or decreased at higher temperatures. If there was an impact on bioaccumulation, moderately lipophilic MPs (log Kow 3.6 -4.6) were generally affected by tDOM addition and more lipophilic MPs (log Kow 3.8 to 6.4) were generally affected by increased temperature. This study suggest that both increased temperatures and addition of tDOM likely will affect bioaccumulation patterns of MPs in shallow coastal regions, albeit with counteracting effects.